Analisis Disiplin Kerja Pada CV Arsana Sentosa - Aniqa Asriah; Enjang Suherman (Lembaga Pengembangan Kinerja Dosen, 2024)
The purpose of this research is to understand the process of employee discipline at CV. Arsana Sentosa, identify barriers in the implementation of employee discipline, and find ways to overcome these barriers. The method used is qualitative descriptive analysis. The analysis results show that the implementation of Standard Operational Procedures (SOP) at CV. Arsana Sentosa provides significant benefits if done properly according to their functions. If employee discipline at CV. Arsana Sentosa decreases, the profit obtained will also decrease, even leading to losses. From previous discussions, it can be concluded that the implementation of discipline at CV. Arsana Sentosa, particularly in the use of fire extinguisher cylinders, has a significant impact if employees implement discipline well. This can be seen from the discipline system at CV. Arsana Sentosa, which is in line with the applicable regulations. However, there are still things that need to be improved, such as employees needing to have principles in managing time and being perfectionists without delaying tasks.